Marital Conflict and Emotional Insecurity Among Chinese Adolescents: Cultural Value Moderation. (2nd February 2015) - Li, Yan; Cheung, Rebecca Y. M.; Cummings, E. Mark
Abstract : Emotional security theory has received substantial empirical support in the literature. However, the applicability of this theory in diverse cultures is still unclear. This study examined emotional insecurity among Chinese adolescents ( N = 315) and how social harmony values moderated the association between parental conflict tactics (233 mothers; 224 fathers) and adolescents' emotional insecurity. Results showed that emotional insecurity could be reliably measured among Chinese adolescents. Furthermore, a significant moderation showed that paternal conflict tactics were associated with adolescents' emotional insecurity only when they endorsed higher social harmony. In the maternal model, an overall association between maternal conflict tactics and adolescents' emotional insecurity was observed. The current findings enrich the literature on emotional security in diverse ecological contexts.